Improving kidney care for people with severe mental health difficulties: a thematic analysis of twenty-two healthcare providers’ perspectives - Cogley, Clodagh; Carswell, Claire; Bramham, Jessica; Bramham, Kate; Smith, Aoife; Holian, John; Conlon, Peter; D’Alton, Paul (Frontiers in Public Health, 2023)
Introduction People with severe mental health difficulties (SMHDs) and concurrent kidney disease have less access to quality kidney care and worse clinical outcomes. Our research investigates the barriers and facilitators to effective kidney care for people with SMHDs, and how care might be improved for this underserved population. Methods We conducted semi-structured interviews with twenty-two physical (n = 14) and mental (n = 8) healthcare professionals with experience working with people with SMHDs and concurrent kidney disease. Interview data were analysed and interpreted using reflexive thematic analysis. Results Four themes were generated from the data: 1. “It’s about understanding their limitations and challenges, without limiting their rights” describes how some people with SMHDs need additional support when accessing kidney care due to challenges with their mental state, motivation, cognitive difficulties, or mistrust of the healthcare system. 2. “There are people falling through the cracks” describes how the separation of physical and mental healthcare, combined with under-resourcing and understaffing, results in poorer outcomes for people with SMHDs. 3. “Psychiatry is a black spot in our continuing medical education” describes how many renal healthcare providers have limited confidence in their understanding of mental health and their ability to provide care for people with SMHDs. 4. “When they present to a busy emergency department with a problem, the staff tend to go ‘…psych patient”” describes how stigma towards people with SMHDs can negatively impact quality of care. Conclusion Healthcare professionals accounts’ describe how people with SMHDs and kidney disease can have favourable outcomes if they have appropriate hospital, community and social supports. Findings indicate that effective management of kidney disease for people with SMHDs requires integrated physical and mental health care, which takes an individualised “whole person” approach to addressing the interaction between kidney disease and mental health.